Review of The Gen Z’s Workforce Qualifıcations and The Effects of Covid-19 on Business Life of Gen Z - Emiroglu, Begum Dilara (My University, 2021)
Generation represents a group of people of the same age who experience similar social events in a\rsimilar social position. Generation theory generally emphasizes that each generation has its own features and\rcharacteristics. Generations differ from each other in terms of the characteristics, values, beliefs, interests and\rexpectations of the members of each generation. These differences between generations cause that people\rworking in the workplaces differ from each other in terms of leadership, attitudes and behaviours, and if this\rsituation is not managed well, it leads to negative consequences for businesses. Gen Z, which represents a\rgeneration born from the mid-1995s to the early 2010s, differs significantly from other generations in terms\rof their unique individual characteristics and workforce qualities. Gen Zers will represent a significant part of\rthe labor market in the coming years. However, the Covid-19 pandemic has changed the destinies of many\rGen Z members, who have just begun to enter the labor market in recent years, towards their business lives.\rDuring the pandemic process, many Gen Z employees have been laid off more than other generations, their\rjob interviews and internships have been cancelled, and they have faced situations such as reduced salaries\rand working hours, unhappiness, anxiety, depression and stress. Therefore, understanding the qualifications\rof Gen Z in the workforce and the effects of the pandemic on the business life of Gen Z individuals are of\rgreat importance for the present and future success of the businesses. For all these reasons, this study aims to\rreveal the characteristics of the Gen Z individuals in the labor market, especially in the tourism sector, and\rthe effects of the Covid-19 pandemic on the business life of Gen Z, through a traditional literature review,\rwhich is one of the exploratory research types. In this context, the research focused on the qualifications of\rGen Z employees in the workforce, especially in the tourism sector, and the effects of the Covid-19 pandemic\ron the Gen Z employees, and the findings obtained from the whole study were summarized in the results\rsection and various suggestions were made on the subject.
Keywords: Otelcilik; Konaklama; Spor ve Turizm; İşletme; Kamu Yönetimi; Sosyoloji